MVP enhances FGF21‐induced ferroptosis in hepatocellular carcinoma by increasing lipid peroxidation through regulation of NOX4 - Jinkun Xia; Boqi Fu; Zhe Wang; Gaolin Wen; Quanshui Gu; Dayu Chen; Haozhen Ren (Wiley, 2024)
Abstract Ferroptosis is a novel, iron‐dependent regulatory cell death mainly caused by an imbalance between the production and degradation of intracellular reactive oxygen species (ROS). Recently, ferroptosis induction has been considered a potential therapeutic approach for hepatocellular carcinoma (HCC). Fibroblast growth factor 21 (FGF21) is a new modulator of ferroptosis; however, the regulatory role of FGF21 in HCC ferroptosis has not been investigated. In this study, we explored the role of FGF21 and its underlying molecular mechanism in the ferroptotic death of HCC cells. We identified Major vault protein (MVP) as a target of FGF21 and revealed that knockdown of MVP inhibited the lipid peroxidation levels of HCC cells by decreasing NADPH oxidase 4 (NOX4, a major source of ROS) transcription, thereby attenuating the effect of FGF21‐mediated ferroptosis. On the other hand, MVP overexpression showed the opposite results. Mechanistically, MVP binds to IRF1 and thus interferes with the interaction between IRF1 and the YAP1 promoter, leading to an increase in NOX4 transcription. Importantly, forced expression of IRF1 or downregulation of YAP1 partially reversed the effect of MVP overexpression on HCC ferroptosis. Furthermore, the results in xenograft tumor models suggested that overexpression of MVP can efficiently increase the level of lipid peroxidation in vivo. Taken together, these results provide new insights into the regulatory mechanism of ferroptosis in HCC.